PENERBITAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG NOMOR 1 TAHUN 2020 SEBAGAI STRATEGI KEBIJAKAN PAJAK PEMERINTAH INDONESIA DALAM MENGHADAPI DAMPAK PANDEMI COVID-19 TERHADAP KEUANGAN NEGARA - Anton Aulawi (FKIP, Universitas Banten Jaya, 2020)
The impact of the Covid-19 pandemic has greatly affected global and national economic order. The existence of physical distancing policies, as well as large-scale social restrictions, greatly affected the activities of tourism and manufacturing sectors, causing the economic growth to slow down. Therefore, the government issued a tax policy by stimulating Government Regulation in Lieu of Law Number 1 of 2020 concerning State Financial Policy and Financial System Stability for Handling the Corona Virus Disease (Covid-19) Pandemic on March 31, 2020 and Regulation of the Minister of Finance which regulates tax incentives known as tax relaxation. This research was conducted using qualitative method A qualitative method was used to produce in-depth descriptions of speech, writing and observable behavior of an individual, community group and organization in a certain context that was studied from a comprehensive and holistic point of view. The results of this study were that the Indonesian Government has established various tax policy strategies during the Covid-19 pandemic which aim to achieve the target of state revenue, by revising tax revenue targets, rearranging state revenue allocations in the 2020 State Revenue and Expenditure Budget and implementing taxes. Trading Through Electronic Systems. The government has also relaxed the imposition of Article 21 Income Tax, Article 22 Income Tax, Article 25 Income Tax, and specific VAT tax returns to the manufacturing sector. So the relaxation of income tax in articles 21, 22 and 25 as well as tax returns was the most effective and appropriate way to overcome the impact of Indonesia's economy in the face of the Covid-19 outbreak.